2005
DOI: 10.1007/s00125-005-1933-x
|View full text |Cite
|
Sign up to set email alerts
|

Severe hypoglycaemia post-gastric bypass requiring partial pancreatectomy: evidence for inappropriate insulin secretion and pancreatic islet hyperplasia

Abstract: These findings suggest that gastric bypass-induced weight loss may unmask an underlying beta cell defect or contribute to pathological islet hyperplasia, perhaps via glucagon-like peptide 1-mediated pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
284
2
12

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 328 publications
(305 citation statements)
references
References 14 publications
7
284
2
12
Order By: Relevance
“…11,30,31 In 2005, Service et al 30 reported in the New England Journal of Medicine 11 the details of six such cases, which these authors deemed adultonset nesidioblastosis, and which were severe enough to require partial pancreatectomy. Several other groups have since reported similar observations.…”
Section: Mechanisms Of Diabetes Improvement Following Bariatric Surgerymentioning
confidence: 99%
See 3 more Smart Citations
“…11,30,31 In 2005, Service et al 30 reported in the New England Journal of Medicine 11 the details of six such cases, which these authors deemed adultonset nesidioblastosis, and which were severe enough to require partial pancreatectomy. Several other groups have since reported similar observations.…”
Section: Mechanisms Of Diabetes Improvement Following Bariatric Surgerymentioning
confidence: 99%
“…Several other groups have since reported similar observations. [31][32][33][34][35][36] At a recent meeting devoted to this topic at Harvard, B135 cases of severe, lateonset, post-RYGB hyperinsulinemic hypoglycemia were discussed, many with intractable neuroglycopenic episodes necessitating pancreatectomy.…”
Section: Mechanisms Of Diabetes Improvement Following Bariatric Surgerymentioning
confidence: 99%
See 2 more Smart Citations
“…One mechanism postulated to improve diabetes after gastric bypass is an augmented incretin response; postprandial plasma concentrations of the potent incretin glucagon-like peptide-1 rise after gastric bypass [2]. Recently hyperinsulinaemia and hypoglycaemia have been recognised as new complications of gastric bypass [3,4]. Patients have presented with hypoglycaemia associated with confusion, syncope and seizures attributed to changes in glucose homeostasis [5].…”
Section: Introductionmentioning
confidence: 99%